Personalistic family educational conditionsin the context of parental professional aspirations - Paulina Dróżdż (Studia z Teorii Wychowania)
The aim of this article is to answer the question of how parental professional aspirations influence the upbringing level, realized in the Polish families. This problem is most acute in the context of labour migration, hence this issue is of central importance in this study. A personalistic view of the issue allows for drawing more profound conclusions than sociological research.